HUBUNGAN ANTARA AKTIVITAS FISIK DENGAN ATENSI PADA REMAJA - Adelia Nurfayza (2023)
Background: Unlike a few decades ago, today's youth are becoming increasingly inactive as a result of technological advances. Physical activity during childhood and adolescence can lead to a significant increase in attention, particularly in movement development. Purpose: This study aims to determine whether there is a relationship between physical activity and attention in adolescents. Methods: This study used a cross-sectional study with a correlative approach. The sample in this study was 155 students of class XI at SMA Budhi Warman 2 Jakarta. The parameters used to measure physical activity are the IPAQ-SF questionnaire and attention using the Stroop Effect Test. Data were analyzed through statistical tests using SPSS 25.0. Results: This study found that the highest level of student activity was in the medium category, 44.5%. The results of the Spearman correlation test, obtained p = 0.008 on the variable physical activity and reaction time, then physical activity and the stroop effect test obtained a value of p = 0.036 so that p <0.05 with a correlation coefficient on the physical activity variable, namely r = 1 and the reaction variable time r = 0.212 and for the stroop effect test score r = 0.168, this value indicates a fairly strong correlation between physical activity and attention. Conclusion: The conclusion from this study is that there is a significant relationship between physical activity and unidirectional attention.